“Now What?”: Exploring Newcomer Youth’s Transition from High School to Postsecondary Education (Canadian Journal of Counselling and Psychotherapy, 2019)
For newcomer youth (i.e., those who have recently migrated to Canada with their families), high school integration has a marked influence on postsecondary preparation. This descriptive phenomenological study aimed to answer the following research question: How do newcomer youth’s experiences in high school impact their transition to postsecondary education? In total, 10 participants, ages 18 through 24, completed in-depth qualitative interviews. Data analysis revealed 5 structures: 3 related to decision-making processes (i.e., high school influence, personal ambitions, and family factors), and 2 centred on experiences in postsecondary education (i.e., areas of growth and postsecondary challenges). Results point to the need for increased support for newcomer youth both in high school and university.